2010
DOI: 10.1126/scisignal.2001180
|View full text |Cite
|
Sign up to set email alerts
|

HCMV-Encoded Chemokine Receptor US28 Mediates Proliferative Signaling Through the IL-6–STAT3 Axis

Abstract: US28 is a viral G protein (heterotrimeric guanosine triphosphate-binding protein)-coupled receptor encoded by the human cytomegalovirus (HCMV). In addition to binding and internalizing chemokines, US28 constitutively activates signaling pathways linked to cell proliferation. Here, we show increased concentrations of vascular endothelial growth factor and interleukin-6 (IL-6) in supernatants of US28-expressing NIH 3T3 cells. Increased IL-6 was associated with increased activation of the signal transducer and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
233
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 190 publications
(252 citation statements)
references
References 66 publications
16
233
2
1
Order By: Relevance
“…Survivin also modulates cell proliferation; human cytomegalovirus was recently shown to mediate endothelial cell proliferation and angiogenesis associated with survivin expression (34,35). However, we observed no difference in expression of the Ki67 proliferation marker in VZV-infected and uninfected skin xenografts (36).…”
Section: Discussioncontrasting
confidence: 51%
“…Survivin also modulates cell proliferation; human cytomegalovirus was recently shown to mediate endothelial cell proliferation and angiogenesis associated with survivin expression (34,35). However, we observed no difference in expression of the Ki67 proliferation marker in VZV-infected and uninfected skin xenografts (36).…”
Section: Discussioncontrasting
confidence: 51%
“…Multiple studies have demonstrated the presence of T cell reactivity to CMV in seronegative patients; this observation, although uncommon, may suggest that CMV infection of certain cell types (e.g. in association with some tumors) or with latency may fail to maintain serologic evidence of infection (155).…”
Section: Humoral Immunitymentioning
confidence: 99%
“…CMVinduced production of inflammatory cytokines such as IL-12, IL-18, TNF-a, and IFN-c by SMCs, macrophages and ECs may contribute to proatherosclerotic effects (170). Slinger et al showed that US28 of HCMV activates the IL-6-JAK1-STAT3 signaling axis through activation of the transcription factor NF-kB and the consequent production of IL-6 and cell proliferation of HCMV-infected tumor cells including glioblastoma (155).…”
Section: Cytokine Production In CMV Infectionmentioning
confidence: 99%
“…10 Other groups also described CMV viral material in glioma samples using similar methodology. 11,12 Mitchell et al found that a large percentage of GBM samples were positive for CMV immediate-early (IE)1, pp65 or glycoprotein B using IHC, ISH and polymerase chain reaction (PCR). 13 However, subsequent to these initial reports, other groups published reports of no detectable CMV protein or genomic material in glioma samples.…”
Section: Detection In Gliomasmentioning
confidence: 99%